(untitled) (Research, Society and Development, 2021)
The study aims to present the most recent literature on the theme of innovation and technology applied to agribusiness. The work consisted of carrying out an analysis of the scientific articles published in the Web of Science database in the period from 2016 to 2020. This is an exploratory research, with a quantitative approach, using the Consolidated Meta-Analytical Approach Theory, which provides an integrative approach to literature review. The results showed that 2,427 scientific articles, national and international, in several languages and in different areas of knowledge, adopted a simultaneous approach of the keywords innovation, technology and agribusiness, in the period from 2016 to 2020. Among these studies, 104 articles were highlighted by Brazilian researchers. The Brazilian Agricultural Research Corporation, Universidade de São Paulo and Universidade Estadual Paulista were the Brazilian institutions that stood out the most in academic production, presenting works shared with Brazilian and foreign organizations, which contributed to the dissemination of knowledge on innovation and technology in agribusiness sector.